Introduction to Research Methods - Tracton-Bishop, Beth (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In this course the student will: a. learn the reasons for conducting social research and the potential uses of such research; b. learn the ethical and conceptual dilemmas that research need to consider; c. learn the language of research methodology and the key tools for collecting data; d. and learn the fundamentals of SPSS and data analysis and display. "